A robust molecular unit nanogrid servicing as network nodes via molecular installing technology. (9th August 2016) - Zhang, Guangwei; Wei, Ying; Wang, Jishu; Liu, Yuyu; Xie, Linghai; Wang, Long; Ren, Baoyi; Huang, Wei
Abstract : A nanogrid that consists of four fluorenes and two carbazoles has been synthesized by molecular installing technology from an L-shaped synthon. Abstract : Organic square nanogrid units have been designed in order to create molecular system nodes and their networks. A nanogrid that consists of four fluorenes and two carbazoles has been synthesized by molecular installing technology from an L-shaped synthon at a total yield of 21%. The fluorene-based nanogrids showed excellent thermal, electrochemical and spectral stability. Nanogrids will be one robust platform to polynodes for the exploration of molecular consciousness, intelligence and robotics.